Numerical simulations of bone remodelling and formation following nucleotomy. (9th May 2019) - Calvo-Echenique, Andrea; Bashkuev, Maxim; Reitmaier, Sandra; Pérez-del Palomar, Amaya; Schmidt, Hendrik
Abstract: Nucleotomy is the gold standard treatment for disc herniation and has proven ability to restore stability by creating a bony bridge without any additional fixation. However, the evolution of mineral density in the extant and new bone after nucleotomy and fixation techniques has to date not been investigated in detail. The main goal of this study is to determine possible mechanisms that may trigger the bone remodelling and formation processes. With that purpose, a finite element model of the L4–L5 spinal segment was used. Bone mineral density (BMD), new tissue composition, and endplate deflection were determined as indicators of lumbar fusion. A bone-remodelling algorithm and a tissue-healing algorithm, both mechanically driven, were implemented to predict vertebral bone alterations and fusion patterns after nucleotomy, internal fixation, and anterior plate placement. When considering an intact disc height, neither nucleotomy nor internal fixation were able to provide the necessary stability to promote bony fusion. However, when 75% of the disc height was considered, bone fusion was predicted for both techniques. By contrast, an anterior plate allowed bone fusion at all disc heights. A 50% disc-height reduction led to osteophyte formation in all cases. Changes in the intervertebral disc tissue caused BMD alterations in the endplates. From this observations it can be drawn that fusion may be self-induced by controlling the mechanical stabilisation without the need of additional fixation. The amount of tissue to be removed to achieve this stabilisation remains to be determined.